2021
DOI: 10.3390/su132112022
|View full text |Cite
|
Sign up to set email alerts
|

Do Companies in Different Industries Respond Differently to Stakeholders’ Pressures When Prioritising Environmental, Social and Governance Sustainability Performance?

Abstract: Good sustainability decisions depend on how companies respond to wide-ranging exposure to exogenous and endogenous pressures. The purpose of the article was to determine whether companies in different industries respond differently to stakeholders’ pressures when prioritising Environmental, Social and Governance sustainability performance (ESG-SP) activities. Data of six sectors, with a total of 75 companies was extracted from the CSRHub database, which is a rating agency that focuses on assessing ESG performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 98 publications
0
9
0
Order By: Relevance
“…Studies in the corporate strategy cluster have considered ESG disclosure as a strategic approach integrated into a business strategy to improve corporate engagement with stakeholders [21,67] and corporate commitments toward the environment [2,63].…”
Section: The Most Frequent Abstractmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies in the corporate strategy cluster have considered ESG disclosure as a strategic approach integrated into a business strategy to improve corporate engagement with stakeholders [21,67] and corporate commitments toward the environment [2,63].…”
Section: The Most Frequent Abstractmentioning
confidence: 99%
“…In the financial performance cluster, studies have mainly focused on analyzing the impact of ESG disclosure on corporate performance [17][18][19][20][21]. Some studies have focused only on developed countries [68,69] or emerging markets [5,42,60], whereas others have compared developed and developing countries [26,70].…”
Section: The Most Frequent Abstractmentioning
confidence: 99%
See 1 more Smart Citation
“…The dependent variable of this study is the number of female board members and independence ownership [13]. The independent variable is ESG ratings consisting of environment, community, employee, and governance disclosure ratings [14,15]. The control variable used is profitability using the return on asset indicator; and solvency using indicators of debt on equity ratio [16,17].…”
Section: Data and Descriptive Statisticmentioning
confidence: 99%
“…These findings prompt the question of whether investors' reactions to environmental activities truly differ by industry. While some studies have reported significant correlations between social activities and business performance, the results are inconclusive regarding the impact of specific industries (e.g., Matakanye et al, 2021;Tamimi & Sebastianelli, 2017;Tuppura et al, 2016;Yoon et al, 2018).…”
Section: Introductionmentioning
confidence: 98%